UMP celebrates the achievements of postgraduates - Kalpana, Ramachandran (2023)
KUANTAN, 12 January 2023 - Universiti Malaysia Pahang (UMP) celebrated the achievements of its graduates for the year 2022 in the Postgraduate Alumni Friendly Ceremony organized by the Institute of Postgraduate Studies (IPS).